The Impact of Dams: A Study with Special Reference to the Dams on the Western Ghats of Idukki District, Kerala - Johnson V (International Journal of Research in Engineering, IT and Social Sciences, 2018)
Dams are large socio-economic investments intended to facilitate domestic and industrial water supply, energy production, irrigation and flood control. Water resources projects such as dams represent large-scale engineering works or activities that can cause significant impacts on socio-economic components of the environment. The socio-economic benefits of dams are numerous and in many places dams have undoubtedly contributed to economic development. The economic benefits of dams have been assumed to outweigh the costs, thus providing rationale for construction of dams around the world. However, the development of these structures can be accompanied by negative biophysical, socio-economic, and geopolitical impacts; often through the loss of ecosystem services provided by fully functioning aquatic systems. The impacts of dams can be involuntarily imposed on marginalized peoples whose livelihoods are dependent on riverine resources. More over dams are more likely to transform rivers and landscapes and create risks of irreversible impact. The paper attempts to analyse whether these impacts that prevail elsewhere is true in the case of dams in the eastern Ghats of Idukki districts in Kerala.